If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x = 5x + -12 Reorder the terms: 9x = -12 + 5x Solving 9x = -12 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 9x + -5x = -12 + 5x + -5x Combine like terms: 9x + -5x = 4x 4x = -12 + 5x + -5x Combine like terms: 5x + -5x = 0 4x = -12 + 0 4x = -12 Divide each side by '4'. x = -3 Simplifying x = -3
| -6-21=3p-12 | | 0.4(x+5)-0.3x=1 | | 3x-(x-3)=13 | | 8(x+7)=136 | | 12x=16x | | Y-16=-3 | | 3x-4=3x-4 | | -22=4x-4(x+6) | | c-5=25 | | 2.5=.05x | | 2-4x=3x+7 | | 4x^2+10x-96=0 | | c+15=4c-45 | | x^2-17x+66=0 | | 55-x=21 | | 5-c=25 | | 2x^2+2xy-3x-3y= | | 7(n+4)=21 | | 5-m=12 | | 4-(2x-8)=12 | | 3(n-5)=-2 | | 0=(2x-5)(x+3) | | 3a-9=15 | | 4+2(2x-8)=12 | | 5y+3-7y=15 | | k-(-13)=8 | | 8(z+10)+2=98 | | 8x^2+3=3 | | 3c-4c+1=5c+2+e | | 0.3X-1.1-x=0.3 | | .5(4x+7)=12 | | 2x^2+7xy+6y^2= |